Conscious Self-regulation and School Engagement as Resources for Students’ Subjective Well-being - T.G. Fomina; E.V. Filippova; V.I. Morosanova (Психолого-педагогические исследования)
The results of an empirical study are presented within the framework of a topical problem of searching for psychological resources for the schoolchildren’ subjective well-being. The resource approach to the study of conscious self-regulation (SR) of achieving goals (V.I. Morosanova) served as the theoretical basis for research. The study had its purpose to assess the contribution of conscious SR and school engagement as resources for the subjective well-being of the 5-11 grade students (N=718). The study implemented the “Multidimensional scale of school engagement” (T.G. Fomina, V.I. Morosanova), Morosanova’s “Self-Regulation Profile of Learning Activity Questionnaire”, and “Multidimensional Students’ Life Satisfaction Scale” (O.A. Sychev et al.). It has been established that the level of conscious SR development and the level of school engagement make a significant contribution to maintaining the students’ subjective well-being in the educational environment. New data have been obtained to clarify that general level of conscious SR development and individual regulatory competencies (planning, modeling, programming, results evaluation) serve as the mediators of the school engagement influence on the students’ subjective well-being. Expanding the understanding of the determinants of students’ subjective well-being, the results obtained provide new arguments in favor of the previously developed idea that conscious SR as a meta-resource not only contributes to the success of solving various life problems, but also enhances the influence of other psychological resources on it. In practical terms, the study results substantiate the productivity of psychological and pedagogical interventions aimed at developing conscious SR and maintaining school engagement as significant resources for subjective satisfaction with the educational environment in adolescent students.